Makna Idiomatikal Idiom Pada Manga One Piece Vol. 91 Karya Eiichiro Oda - Ikhsan Maulana Fadlilah; Anisa Arianingsih; Soni Mulyawan Setiana (Program Studi Sastra Jepang, Universitas Komputer Indonesia Bandung, 2020)
This study aims to describe the meaning of idioms in the manga One Piece Vol. 91 which is one of the popular manga with a high frequency of idioms. The method used in this research is descriptive analysis method. The results of this study found 13 idioms which is ki ga tsuku means